The Influence of Price, Promotion, and Brand Image on the Purchase Decision of Rocket Chicken Products in Gresik City - Sabrina Dewanti Mugiyono; Adiba Fuad Syamlan; Mochamad Syafii (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to examine the effects of price, promotion, and brand image on the purchase decision of Rocket Chicken products in Gresik City. Using a quantitative approach and explanatory research design, data were collected through a survey involving 250 consumers who had purchased Rocket Chicken products in the last six months. Data collection was conducted using a questionnaire that measured consumer perceptions of price, promotion, brand image, and purchase decision using a 5-point Likert scale. The data analysis results using multiple linear regression showed that price, promotion, and brand image significantly and positively influenced purchase decisions. Among the three variables, brand image had the most dominant effect, followed by price and promotion. These findings indicate that consumers not only consider the price of the product but also pay attention to the attractiveness of promotions and brand image when making purchase decisions. Based on these findings, it is suggested that Rocket Chicken strengthen its brand image through consistent product quality and service experience, offer attractive promotions, and keep prices competitive to attract more consumers. This study makes an important contribution to understanding the factors that influence purchase decisions in the local fast food industry, particularly in Gresik City, and can serve as a reference for brand managers in formulating more effective marketing strategies.